2005
DOI: 10.1111/j.1463-1326.2005.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early addition of rosiglitazone to sulphonylurea therapy in older type 2 diabetes patients (>60 years): the Rosiglitazone Early vs. SULphonylurea Titration (RESULT) study

Abstract: Aim: To compare the efficacy, safety and tolerability of adding rosiglitazone (RSG) vs. sulphonylurea (SU) dose escalation in older type 2 diabetes mellitus (T2DM) patients inadequately controlled on SU therapy. Methods: A total of 227 T2DM patients from 48 centres in the USA and Canada, aged !60 years, were randomized to receive RSG (4 mg) or placebo once daily in combination with glipizide 10 mg twice daily for 2 years in a doubleblind, parallel-group study. Previous SU monotherapy was ¼ to ½ maximum recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 22 publications
4
41
0
2
Order By: Relevance
“…Adjustment for change in HbA1c did not affect the finding [78]. In a subgroup analysis of the PREDICTIVE study evaluating individuals in a clinical practice setting who transferred from an OAD-only regimen to an OAD plus insulin detemir, NPH insulin or insulin glargine, all subgroups combined lost an average of 0.9 kg of body weight (p < 0.0001) [47].The clinical efficacy of rosiglitazone and pioglitazone as monotherapy or combination therapy with insulin, sulphonylureas or metformin is well established [79][80][81]. A class effect of TZDs, however, is treatment-associated weight gain and large, longitudinal studies such as ADOPT, DREAM and PROactive have shown that these agents can cause appreciable weight gain of up to 4-5 kg [41,42,44].…”
mentioning
confidence: 96%
“…Adjustment for change in HbA1c did not affect the finding [78]. In a subgroup analysis of the PREDICTIVE study evaluating individuals in a clinical practice setting who transferred from an OAD-only regimen to an OAD plus insulin detemir, NPH insulin or insulin glargine, all subgroups combined lost an average of 0.9 kg of body weight (p < 0.0001) [47].The clinical efficacy of rosiglitazone and pioglitazone as monotherapy or combination therapy with insulin, sulphonylureas or metformin is well established [79][80][81]. A class effect of TZDs, however, is treatment-associated weight gain and large, longitudinal studies such as ADOPT, DREAM and PROactive have shown that these agents can cause appreciable weight gain of up to 4-5 kg [41,42,44].…”
mentioning
confidence: 96%
“…In one recent randomized study in 227 subjects, rosiglitazone or placebo was given to a group of mostly elderly patients, many of whom had some baseline peripheral edema. 98 Although the incidence of pedal edema increased in the group taking the TZD (23% vs. 9%), the number of patients reporting adverse events related to congestive heart failure (CHF) was similar (3.4% vs. 2.7%). Thus, it is advisable to be cautious in the use of TZDs in patients with established heart disease, and in the evaluation of peripheral edema, which in most cases represents benign fluid retention and not actual heart failure.…”
Section: Fluid Retentionmentioning
confidence: 95%
“…For example, in a 2-year study, early addition of rosiglitazone to sulphonylurea therapy significantly reduced disease progression, enabling an increased proportion of patients to achieve HbA 1c goals compared with uptitration of sulphonylurea ( Figure 3A, 3B), without any increase in Table 1 Number of antihypertensive agents required to achieve target blood pressure (39)(40)(41)(42) MDRD (39) ABCD ( adverse events (54). Furthermore, medical resource utilisation decreased with combination therapy ( Figure 3C) (55).…”
Section: Combination Therapy Using Agents With Complementary Modes Ofmentioning
confidence: 99%